Active roof-contact: The future development of cemented paste backfill. (17th March 2023) - Yin, Shenghua; Yan, Zepeng; Chen, Xun; Yan, Rongfu; Chen, Dapeng; Chen, Junwei; Li, Gongcheng
Highlights: Poor roof-contact of backfill can pose a serious threat to personnel. Expansion agent can make CPB actively contact the roof. The mechanism of expansion backfill technology is "expansion-extrusion-bonding". MgO-based expansion agent makes up for the defect of excessive water demand in the expansion matrix. Abstract: Cemented paste backfill (CPB) technology may significantly change and enhance the role of tailings in the mining industry. However, poor roof-contact of backfill can pose a serious threat to personnel. The expansion agent (EA) in civil engineering can make CPB actively contact the roof. Therefore, we intend to evaluate the potential application of expansion CPB technology. This paper reviews the development history of CPB technology and the problems in filling roof-contact, with particular emphasis on the principle of expansion backfill technology, i.e., the mechanism of "expansion-extrusion-bonding". The mechanism of some concrete EA and the properties of the expansion matrix are compared and analyzed. Finally, the future research directions of the expansion backfill technology are foreseen. The results of various studies demonstrate that MgO-based EA makes up for the defect of excessive water demand in the expansion matrix and has little effect on the compressive strength. Moreover, the comprehensive analysis of the expansion material characteristics in this review may form the basis for future industrial application research on the expanded backfill.